2008
DOI: 10.1007/s00268-008-9552-6
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Neutrophil‐to‐Lymphocyte Ratio as a Prognostic Predictor after Curative Resection for Hepatocellular Carcinoma

Abstract: Preoperative NLR >or= 5 was an adverse predictor of disease-free and overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
347
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(361 citation statements)
references
References 57 publications
12
347
2
Order By: Relevance
“…From then on, a large number of clinical studies have been performed to understand the neutrophil-cancer relationship. Clinical data have often related elevated circulating neutrophil counts or elevated neutrophil-to-lymphocyte ratios (NLRs) as a predictive parameter for poor outcome and formation of distant metastasis in patients with epithelial malignancies [367], including lung [368,170], gastric [159,163,369], renal cell carcinoma [370], ovarian [141], hepatic [143,148,371], pancreatic [138], colon cancer [145,372], and colorectal carcinoma [152] (Table 3). However, Caruso et al [200] observed that when analyzing the amount of tumor-infiltrated neutrophils in advanced gastric carcinoma, in female but not male, patients with higher TANs had a favorable prognosis.…”
Section: Prognostic Values Of Neutrophils and Other Myeloid Subtypes mentioning
confidence: 99%
See 1 more Smart Citation
“…From then on, a large number of clinical studies have been performed to understand the neutrophil-cancer relationship. Clinical data have often related elevated circulating neutrophil counts or elevated neutrophil-to-lymphocyte ratios (NLRs) as a predictive parameter for poor outcome and formation of distant metastasis in patients with epithelial malignancies [367], including lung [368,170], gastric [159,163,369], renal cell carcinoma [370], ovarian [141], hepatic [143,148,371], pancreatic [138], colon cancer [145,372], and colorectal carcinoma [152] (Table 3). However, Caruso et al [200] observed that when analyzing the amount of tumor-infiltrated neutrophils in advanced gastric carcinoma, in female but not male, patients with higher TANs had a favorable prognosis.…”
Section: Prognostic Values Of Neutrophils and Other Myeloid Subtypes mentioning
confidence: 99%
“…[148] Hepatocellular carcinoma (HCC) Patients with an NLR>2.5 showed higher risk for tumor recurrence in HCC patients undergoing liver transplantation.…”
Section: Prognostic Values Of Neutrophils and Other Myeloid Subtypes mentioning
confidence: 99%
“…Recently, several reports have indicated that the state of the Systemic Inflammatory Response (SIR) provides significant information about the prognoses of a variety of cancers [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] . Neutrophil-lymphocyte ratio (NLR), which reflects SIR, has been reported as a prognostic factor in gastrointestinal cancers, including intrahepatic cholangiocarcinoma 19 and colorectal cancer 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The N/L ratio was calculated from the differential count by dividing the absolute neutrophil count by the absolute lymphocyte count. An N/L ratio ≥5 was considered elevated in accordance with the literature 8, 11, 17, 18…”
Section: Methodsmentioning
confidence: 84%
“…The tumor cells then produce chemokines, cytokines, and prostaglandins, which recruit inflammatory cells, which then subsequently trigger cancer‐related inflammation and further facilitate various tumor‐promoting effects 7. The neutrophil : lymphocyte (N/L) ratio has been shown to reflect the immune response and has been identified as a prognostic marker in many cancers, including gastrointestinal tract malignancy, non‐small cell lung cancer, cervical cancer, hepatocellular carcinoma, pancreatic cancer, ovarian cancer, and soft‐tissue sarcoma, reflecting a consistently decreased survival in patients with a high N/L ratio 8, 9, 10, 11, 12, 13, 14, 15. In addition, N/L ratio is reportedly correlated to incidental microcarcinoma in thyroid goiters, further indicating its potential as a diagnostic marker 16.…”
Section: Introductionmentioning
confidence: 99%